Foreign Businesspeople in Colombia and Local Political Power During the Regeneration (1886-1898). The case of the Antillean merchant Manuel Cortissoz (2022)
The article proposes to approach the complaint made by the foreign businessman Manuel Cortissoz over damages suffered in the war of 1884-85, seeking to identify his connections withthe Santander Regenerator group, which made him into one of the great victors after the end of the war. Making use ofthe prosopographical method and the analytic postulates of microhistory, it will investigate those relationships with the actors of the Regeneration in Santander during this historic moment (1886 - 1898) and attempt to understand the implementation of this political project in the regions. The documentation willpermit the proposal of the hypothesis that, in effect, the close relationship Cortissoz had with the regenerator group not only meant that he would emerge unscathed from the war, but it wasalso crucial at the time of his complaint, which was accepted, despite the many errors in its execution.